Diferencias en los sonidos cardíacos según la anatomía de los caninos (Canis lupus familiaris) (2019)
Auscultation is a fundamental part of the clinical examination of a patient. From the cardiovascular point of view, auscultation is a tool determining factor when issuing a diagnosis, since a good knowledge of the heart sounds allow early identification of the disease cardiovascular